A revenue history of the Sundarbans, from 1765 to 1870 - Pargiter, F. E. (Frederick Eden), 1852-1927, author.
1 online resource (400 pages).
Keywords: The Sundarban stretches from the brackish waters of the broad Hooghly on the west, to the fresh waters of the still broader Meghna to the east; the turbid waters of the Bay of Bengal on its southern limits, to the zamindari or pargana lands on its northern extremity and includes in its southern fringes the dense natural mangrove forests, it is famous for. The revenue history of Sundarbans is linked up with its riverine and coastal networks to its strategic location at the head of the Bay of Bengal which made it a natural protective barrier for the densely populated city of Calcutta. The massive transformation combined with the changed physical structure of Sundarban influenced society and economy on the one hand and invited settlers to establish their control in that region on the other. The text of Pargiter focuses on the revenue history of a larger part of Sundarbans, viz., Jessore, Khulna, Bakarganj and some parts of 24-Parganas since the inception of the colonial rule in Bengal. It has also been shown how the colonial administrators took various types of measures for collecting revenue by the way of land reclamation.The introductory note by the editor analyses the revenue settlement policies which had been implemented on different occasions to ensure the revenue maximization policies of the British Raj on the one hand and to establish an human settlement in the deltaic region on the other. Please note: Taylor & Francis does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka